1985
DOI: 10.1017/s0141347300010041
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Applied Relaxation and Operant Activity Training on Chronic Pain

Abstract: This investigation was designed to evaluate the utility of a behaviour therapy programme provided on an outpatient basis for the management of chronic pain. Twenty-eight chronic pain patients were randomly assigned to one of three groups. The first group served as a waiting-list control and had minimal contact with the clinic during the study, while the second group received the regular treatment regime provided by the rehabilitation clinic. The behaviour therapy group also received some of the regular treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Relaxation therapy has been used for lower back pain (Linton et al, 1985;Nicholas et al, 1992). Massage therapy may effectively treat lower back pain as it has been shown to reduce pain in other painful syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxation therapy has been used for lower back pain (Linton et al, 1985;Nicholas et al, 1992). Massage therapy may effectively treat lower back pain as it has been shown to reduce pain in other painful syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Cairns and Pasino (1977) compared, for example, physical therapy "as usual" with the operant activities programme and found that the operant programme produced activity increases approximately twice as large as did "normal" physical therapy. Sanders (1983) as well as Linton, Melin, and Stjernlöf (1985) have also found that the activities programme produces very substantial improvement.…”
Section: Activities Training Enhances Physical Therapymentioning
confidence: 97%
“…These include, but are not limited to: low impact aerobic exercise (Chou and Huffman 2007 ), stretching/strengthening (Chou and Huffman 2007 ), yoga (Chou and Huffman 2007 ;Cramer et al 2013 ;Büssing et al 2012 ), aquatherapy (Baena-Beato et al 2014 ;Evcik et al 2008 ), mindfulness and acceptance based therapies (Veehof et al 2011 ), relaxation training (Linton 1985 ), biofeedback (Flor and Birbaumer 1993 ), massage (Chou and Huffman 2007 ;Cherkin et al 2003 ), chiropractic (Chou and Huffman 2007 ;Cherkin et al 2003 ), acupuncture (Chou and Huffman 2007 ) and trigger point injections (Scott et al 2009 ). Though the extant literature suggests these interventions demonstrate superiority over nonactive control conditions, it is diffi cult to claim, with any certainty, that any one of these interventions is any better than the other.…”
Section: Complementary and Integrative Carementioning
confidence: 99%